(3GdUjQaI GdGdcJQhfjI (B:s (3GdGOhGJ hGdJWHjbGJ heYjbGJ GdJhSY (B/s - (3GdTeQj, fGXe eMeO fhQjs; (3GdYHOGdGJ, YHO GdaJGM RgjQs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2008)
(3GdaUd GdChd (B: (3fTCI GdUjQaI GdGdcJQhfjI hJWhQgG (B: (3GdeHMK GdChd (B: (3JcfhdhLjG hfXe GdeYdheGJ, Gdeaghe hGdechfGJ (B: (3eaghe JcfhdhLjG GdeYdheGJ (B: (3echfGJ hejRGJ JcfhdhLjG GdeYdheGJ (B: (3GdeHMK GdKGfi (B: (3JWHjbGJ GdUjQaI GdGdcJQhfjI YGdejG (B: (3GSJNOGe THcI GdGfJQfJ (B: (3fXGe GdOaY GdGdcJQhfi (B: (3GdUjQaI GdGdcJQhfjI ai GdOhd GdeJbOeI(B-(3GdaUd GdKGfi (B: (3COhGJ GdUjQaI GdGdcJQhfjI (B: (3GdeHMK GdChd (B: (3GdbfhGJ GdGdcJQhfjI (B: (3Hfc GdGfJQfJ (B: (3GdJYQja hGdNOeGJ GdJi jbOegG GdHfc (B: (3GdeHMK GdKGfi (B: (3GdHWGbGJ GdGdcJQhfjI (B: (3HWGbGJ GdajRG (B: (3JYQja HWGbGJ GdajRG (B: (3GdeHMK GdKGdK (B: (3GOGQI GdUjQaI GdGdcJQhfjI (B: (3eQcR GdHWGbGJ GdGdcJQhfjI(B-(3GdaUd GdKGdK (B: (3GWQGa GdUjQaI GdGdcJQhfjI (B: (3GdeHMK GdChd (B: (3YedGA GdHfhc GdJLGQjI (B: (3GSHGH YOe GdMUhd Ydi GdHWGbI GdGdcJQhfjI (B: (3GdbfhGJ GdJi jSJNOegG GdYedGA hWQb GdJYQa YdjgG (B: (3GdeHMK GdKGfi (B: (3GdHfhc GdJLGQjI (B: (3eYjbGJ GdJhSY ai GdUjQaI GdGdcJQhfjI HGdfSHI ddHfhc GdJLGQjI (B: (3GdeHMK GdKGdK (B: (3GdHfhc GdeQcRjI (B: (3GdHfc GdeQcRj hGdUjQaI GdGdcJQhfjI(B-(3GdaUd GdQGHY (B: (3GdUjQaI GdGdcJQhfjI YQHjG (B: (3GdeHMK GdChd (B: (3gjcd GdLgGR GdeUQai GdGQOfi hGdUjQaI GdGdcJQhfjI (B: (3GdJWhQ GdJGQjNi ddLgGR GdeUQai ai GdGQOf (B: (3GdeHMK GdKGfi (B: (3GdHfc GdeQcRj hGdUjQaI GdGdcJQhfjI (B: (3GLQGAGJ h JTQjYGJ GdHfc GdeQcRj JLGg GdYed GdeUQai GdGdcJQhfis
(3HdjhZQGajG U(B. (3edGMbs
Keywords: (3GbJUGO eGdjs; (3GdHfhc(B--(3eYGdLI GdeYWjGJ EdcJQhfjGs; (3Ydhe eUQajIs; (3eUGQas